2019
DOI: 10.1177/2048872619869328
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Choice– Impact of identifying precipitating factors on 30-day mortality in acute heart failure patients

Abstract: Background: The aim of this study was to describe the prevalence and prognostic value of the most common triggering factors in acute heart failure. Methods: Patients with acute heart failure from 41 Spanish emergency departments were recruited consecutively in three time periods between 2011 and 2016. Precipitating factors were classified as: (a) unrecognized; (b) infection; (c) atrial fibrillation; (d) anaemia; (e) hypertension; (f) acute coronary syndrome; (g) non-adherence; and (h) two or more precipitant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Among the 761 screened citations, 28 studies published over the last 10 years 8,20,24,3559 met the inclusion criteria after full-text review (Figure 1). These 28 studies included 19 different risk models that had been used in AHF patients in the ED setting to predict clinical outcomes (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 761 screened citations, 28 studies published over the last 10 years 8,20,24,3559 met the inclusion criteria after full-text review (Figure 1). These 28 studies included 19 different risk models that had been used in AHF patients in the ED setting to predict clinical outcomes (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…20,35,39,5459,62 In addition, nine studies used at least one risk score to define the severity of AHF decompensation, to produce subgroups of patients based on their risk or to adjust in multivariate regressions (to reduce the impact of confounding factors). 8,24,36,45–50 In one of them, the comparison between discharged and hospitalised patients at similar predicted risk (using the risk model developed by Lee et al.) 24 demonstrated a higher 90-day mortality for patients discharged home from the ED.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Atrial fibrillation (AF) is the most common arrhythmia seen in patients with AHF, and approximately 35-40% of AHF patients have a history of AF at the time of admission. [7][8][9][10] It has also been reported that AF is the second most common precipitating factor of AHF. 11 Although T he impact of heart rate (HR) on prognosis in patients with chronic heart failure (HF) has been extensively investigated, and a lower HR is associated with lower rates of adverse events.…”
mentioning
confidence: 99%
“…An analysis of the data from an extensive Spanish multicentre registry on the epidemiology of acute heart failure in emergency departments (EAHFE) assessed the prevalence and prognostic value of the most common triggering factors in acute heart failure. 16 Infection and atrial fibrillation were the most common precipitants. Among all precipitant factors, an acute coronary syndrome was associated with a markedly increased 30-day mortality, whereas infection and atrial fibrillation were associated with better outcomes.…”
mentioning
confidence: 99%